Comparison of Takhshish al-Qadla on Legal Sanctions for Violation of Marital Law: A Study in Indonesia, Malaysia and Singapore - Ulya, Nanda Himmatul (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
Family law reform in Muslim countries has been carried out since the 7th century until now. The aim is to respond to the development of the times and the concept of classical fiqh which is considered less accommodating in answering current family problems. This study aims to understand the form of takhshish al-qadla in applying sanctions to the Marriage Law in Indonesia, Malaysia, and Singapore. This article is a library research using a comparative approach. The primary legal materials in this study are Law No. 16 of 2019 in conjunction with Law No. 1 of 1974 concerning Marriage, KHI, Enakmen of the Islamic Family Law of Negeri Sembilan 2003 No. 11, and Administration of Muslim Law Act 1966 (2020 revised edition). The analysis results show that the marriage laws in Indonesia, Malaysia, and Singapore contain legal sanctions for citizens who violate these rules. Comparison of the three countries, namely: 1) Indonesia, there are 6 elements included in the criminal provisions with a penalty of a fine of IDR 7,500 or 3 months imprisonment. 2) Enakmen of the Islamic Family Law of Malaysia, 8 provisions included in the penalty section with a maximum fine of RM 1,000 or imprisonment of 6 to 1-year maximum. 3) Singapore in AMLA 1996 (2020 revised edition) imposes sanctions on 6 violations of marriage rules with a maximum fine of 500 (five hundred Singapore dollars) or imprisonment for a period of not more than 6, 12 months to 3 years. The legal sanctions contained in the marriage rules in Indonesia, Malaysia, and Singapore are a form of bakhshish al-qadla carried out by the government to provide legal certainty and threats to comply with the rules, norms, and regulations in force in a country.